COMPARISON OF POST-OPERATIVE OUTCOMES OF MASS CLOSURE CONTINUOUS TECHNIQUE VS HUGHES REPAIR IN PATIENTS UNDERGOING EXPLORATORY LAPAROTOMY - ULLAH , SS; HIRAJ , MURK; SHAH , MF; ZAKRIA , M; SHAHID , M (Biological and Clinical Sciences Research Journal, 2024)
Surgical techniques for abdominal closure following exploratory laparotomy play a crucial role in determining postoperative complications. The mass closure continuous approach and Hughes repair are commonly employed methods with unique characteristics and outcomes. Objective: This retrospective comparative study aimed to evaluate the incidence of postoperative complications associated with the mass closure continuous approach and Hughes repair in patients undergoing exploratory laparotomy. Methods: The study was conducted at Nishtar Hospital Multan from July 2023 to December 2023. A total of 50 patients aged between 18 and 60 years of both genders, undergoing exploratory laparotomy, were included through non-probability sampling. Patients were treated either with the mass closure continuous technique or Hughes repair for abdominal closure. The mean operative time for each technique was recorded. The incidence of postoperative complications, including incisional hernia, wound infection, abdominal burst, and seroma, was assessed. Statistical analysis was performed using appropriate methods. Results: The mean operative time for the mass closure continuous technique was 16.32±2.1 minutes, significantly lower than that of Hughes repair (p<0.0001). Patients treated with Hughes repair demonstrated a significantly lower incidence of incisional hernia, wound infection, abdominal burst, and seroma compared to those treated with the mass closure continuous technique. Conclusion: Hughes’s repair technique for abdominal closure following exploratory laparotomy is associated with reduced occurrence of postoperative complications, including incisional hernia and wound-related issues. Therefore, it may be considered a safe and effective option for abdominal closure in these patients.